KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGEMBANGAN MANAJEMEN BERBASIS SEKOLAH PADA JENJANG SEKOLAH DASAR - Mahadi Kesuma Rambe; Iwan Purnama; Sakinah Ubudiyah Siregar; Marlina Siregar; Aziddin Harahap (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT This study is grounded in the importance of the principal’s role as an educational leader. School program planning constitutes a strategic responsibility aimed at improving educational quality through the implementation of School-Based Management. This study aims to describe the principal’s leadership in planning the development of School-Based Management (SBM) at SD Negeri 01 Pangkatan using a qualitative approach with a descriptive method. The research subjects include the principal, classroom teachers, Physical Education (PJOK) teachers, and educational staff, with data collected through interviews, observations, and documentation. The data were analyzed through stages of data reduction, data display, and conclusion drawing. The findings indicate that the principal’s leadership in planning SBM development is carried out in a participatory manner by involving teachers and educational staff in formulating the school’s vision and mission, designing work programs, and managing school resources. The principal acts as a director, coordinator, and decision-maker, supported by effective communication and coordination, enabling the development of systematic programs aligned with school needs. Therefore, participatory and communicative leadership contributes to enhancing stakeholder involvement and improving the quality of education. ABSTRAK Penelitian ini dilandasi oleh pentingnya peran kepala sekolah sebagai pemimpin dalam dunia pendidikan. Perencanaan program sekolah merupakan tanggung jawab strategis untuk mendorong peningkatan mutu pendidikan melalui penerapan Manajemen Berbasis Sekolah. Penelitian ini bertujuan mendeskripsikan kepemimpinan kepala sekolah dalam merancang pengembangan Manajemen Berbasis Sekolah (MBS) di SD Negeri 01 Pangkatan dengan pendekatan kualitatif metode deskriptif. Subjek penelitian meliputi kepala sekolah, guru kelas, guru PJOK, serta tenaga kependidikan, dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Data dianalisis melalui tahapan reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepemimpinan kepala sekolah dalam perencanaan pengembangan MBS dilaksanakan secara partisipatif dengan melibatkan guru dan tenaga kependidikan dalam perumusan visi dan misi, penyusunan program kerja, serta pengelolaan sumber daya sekolah. Kepala sekolah berperan sebagai pengarah, koordinator, dan pengambil keputusan, didukung oleh komunikasi dan koordinasi yang baik sehingga program sekolah tersusun secara sistematis sesuai kebutuhan. Dengan demikian, kepemimpinan yang partisipatif dan komunikatif berkontribusi dalam meningkatkan keterlibatan warga sekolah dan mutu pendidikan.